2021
DOI: 10.1108/jea-08-2020-0168
|View full text |Cite
|
Sign up to set email alerts
|

Opening the black box of leadership coaching: an examination of coaching behaviors

Abstract: PurposeLeadership coaching is an increasingly popular development tool for school principals. However, specific coaching behaviors are rarely conceptualized or examined in prior research. This study presents a coaching behavior framework and then analyzes actual coaching conversations between principals and coaches to illustrate how specific coaching behaviors create opportunities for principals to reflect and think critically about their leadership.Design/methodology/approachBuilding on theories of interperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Compared to other similar freelance work, such as trainers and workplace counsellors, coaches encounter a more complex multi‐level contracting and negotiation procedures. In contrast to training, conversations and negotiations in the coaching process are often considered “mysterious” as it is taken place in a private one‐on‐one setting (Fleddermann et al, 2023; Patrick et al, 2021). In addition, the sponsoring organisation (i.e., social factors) has a consequential influence on coaching outcomes than workplace counselling given that the ultimate objective of coaching is primarily related to coachees' growth at the workplace.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other similar freelance work, such as trainers and workplace counsellors, coaches encounter a more complex multi‐level contracting and negotiation procedures. In contrast to training, conversations and negotiations in the coaching process are often considered “mysterious” as it is taken place in a private one‐on‐one setting (Fleddermann et al, 2023; Patrick et al, 2021). In addition, the sponsoring organisation (i.e., social factors) has a consequential influence on coaching outcomes than workplace counselling given that the ultimate objective of coaching is primarily related to coachees' growth at the workplace.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, the sponsoring organisation and individuals receiving the training or coaching service have contrasting views on learning objectives and outcome evaluations (Louis & Fatien Diochon, 2014). However, coaches often experience a greater level of anxiety and doubt than other similar helping professionals given that coaching sessions are commonly taken place in a “black box”, that is, a private one‐on‐one conversation (Fleddermann et al, 2023; Patrick et al, 2021). The coach has the main responsibility to ensure an effective three‐way communication and joint alliance among all related parties, such as the coach ‐coachee – sponsoring organisation (de Haan & Nieß, 2015; Lai & Smith, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most coaches aim to facilitate critique of and reflection on current practices, as doing so often provides the best opportunities for growth in organizations. However, one study found that only 1/3 of coaching interactions were coded as this type of interaction [ 11 ]. More generally, many studies have found that much of coaching focuses on the relationship between coach and coachee and a significant portion of the work that occurs is around the building of this relationship [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mentoring, which is provided by the clinical setting principal via a hierarchical relationship (Aguilar, 2013) with the aspirant, a leadership coach typically operates in a non-evaluative manner, focused on aspirant development (Flückiger et al, 2017; Grissom & Harrington, 2010; Patrick et al, 2021; Kappler-Hewitt et al, 2020; Silver et al, 2009; Shoho et al, 2012). Importantly, these coaches tend to be employees of and housed within the preparation program rather than the school district.…”
Section: Introductionmentioning
confidence: 99%
“…Within these programs, these new coaching roles have been enacted to supplement or replace the role of the university-based clinical/field supervisor. Unlike supervisors, these roles have “frequent touch points” (Herman et al, 2022, p. 39) with aspirants to listen and ask questions, provide advice and feedback, and serve as a thought partner in ways that supplement the developmental interactions provided by mentor principals (Cosner et al, 2018; Fusarelli et al, 2019; Flückiger et al, 2017; Grissom & Harrington, 2010; Herman et al, 2022; Jones, 2015 ; Kappler-Hewitt et al, 2020; Patrick et al, 2021; Shoho et al, 2012; Silver et al, 2009). Notably, these roles demonstrate a “shift from a compliance or monitoring-centered approach to supervising clinical experiences, to one focused on supporting candidates’ individual development” (Herman et al, 2022, p. 38).…”
Section: Introductionmentioning
confidence: 99%